Perilaku Perawat dalam Perawatan Paliatif di Era Pandemic Covid-19 - Suprapto Suprapto (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Introduction: patients with palliative care usually experience distress and emotionality, so efforts are needed to improve the quality of palliative care that can be realized with knowledge, attitudes, and skills. Purpose; knowing the relationship between knowledge, attitudes, and practice of nurses in palliative care in hospitals. Method; The research used is a cross-sectional study. The sample uses the total sampling technique. The instrument used was a questionnaire sheet in the form of google from and analyzed by the Spearmen Rank test. Results; based on the descriptive analysis show that there are no differences in knowledge, attitudes, and practices between respondents in hospitals. Conclusion; that there is no significant difference between the knowledge, attitudes, and practice of nurses in providing palliative care to patients in hospitals. Recommendations are expected to always hold or involve nurses in training, seminars, discussions, or workshops on palliative care regularly to improve the knowledge and skills of nurses to improve the quality of nursing services, especially palliative care.